The effects of different club affiliation on BTV subscription - Roque, David José Pereira (2015)
Sports marketing has unique characteristics that may lead their audience in behave in completely different ways compared with all the others consumer’s profiles. BTV challenged the sports viewing industry not only by spoiling their own TV rights but also by including on their target people who support others teams beyond Benfica. In spite of this strategy has been considered at an initial stage as risky, BTV only in the first year accounted 30 Million Euros of revenues. The current study aims to study the impact that all the different sports contents powered by BTV have on BTV subscription, the influence of different club affiliation on BTV subscription and, the influence of price on BTV subscription. On the first part of the study a literature review was performed in order to understand different insights that were revealed as important to justify the results achieved. This was followed by an analyze of the current situation of televised sports industry in Portugal and BTV in particular. Regarding the contents, English Premier League and Benfica games played at home are by far, the contents that arouse more interest. The results reveal that there is a huge influence of different club affiliation on BTV subscription, particularly by Sporting and Porto supporters. The price perception of BTV is also influenced by different club affiliation, where Benfica supporters have different opinion regarding BTV price, when compared in particular with Sporting and Porto supporters. Other conclusions are highlighted on the last part of the dissertation.